Ijtihad Method in Determining of the Fatwa Dewan Syariah Nasional – Majelis Ulama Indonesia (DSN-MUI) - Ahmad Rifat Mathar (Universitas Darunnajah, 2025)
This study explores the ijtihad methodology used by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in formulating fatwas on contemporary Islamic economic and financial issues. Amid rapid advancements in financial products and digital transactions, conventional fiqh often proves inadequate, prompting the need for contextual legal reasoning. The research applies qualitative library research with a descriptive-analytical approach, focusing on content analysis of DSN-MUI fatwas. The study reveals that DSN-MUI employs a distinctive and structured ijtihad framework, known as makharij fiqhiyyah, to formulate relevant and applicable fatwas. This method integrates classical usul fiqh with contextual considerations and comprises four key components: al-Tays?r al-Manhaj? (methodological facilitation), tafr?q al-?al?l ‘an al-?ar?m (distinguishing halal from haram), i‘?dat al-na?ar (re-evaluation of legal opinions), and ta?q?q al-man?? (legal cause verification). The fatwas produced are not only theoretically sound but also function as semi-binding references within Indonesia’s legal framework, reflecting DSN-MUI’s role as a mediator between Islamic legal tradition and the dynamics of the modern financial system. This study contributes to understanding how Islamic legal institutions adapt traditional jurisprudence to meet the demands of contemporary economic realities in a practical and accountable manner